Comparison Analysis of the Integration of Early Warning Systems in the Nordic-Baltic Region - Laurinavičiūtė, Justina (Proceedings of the International ISCRAM Conference, 2026)
This study examines the integration and effectiveness of Early Warning Systems (EWS) across the Nordic–Baltic Eight (NB8) countries, namely Denmark, Estonia, Finland, Iceland, Latvia, Lithuania, Norway, and Sweden. Through a mixed method exploratory design combining national technological data, hazard exposure profiles, and public trust indicators, the analysis reveals a high degree of technological convergence in hazard monitoring, data analytics, and multi-channel risk communication. Despite consistent exposure to major environmental hazards, particularly floods, significant disparities emerge in societal trust and coping capacity, indicating that technological robustness alone does not ensure societal resilience. The findings highlight a gap between institutional capabilities and public perception, with lower trust levels in several countries posing risks to warning compliance and crisis response effectiveness. While regional cooperation and adherence to international standards contribute to uniform EWS structures, uneven societal and infrastructural conditions limit the overall resilience potential. The study concludes that strengthening community engagement, improving risk communication credibility, and tailoring resilience strategies to national and sub national contexts are essential for enhancing the end-to-end performance of EWS in the NB8 region.